Ligand engineering in Cu(ii) paddle wheel metal–organic frameworks for enhanced semiconductivity. Issue 26 (23rd June 2020) - Golomb, Matthias J.; Calbo, Joaquín; Bristow, Jessica K.; Walsh, Aron
Abstract : We report the electronic structure of two metal–organic frameworks with copper paddle wheel nodes connected by a ligand with accessible nitrogen lone pairs. Our study highlights DMOF-1 as a potential semiconductor. Abstract : We report the electronic structure of two metal–organic frameworks (MOFs) with copper paddle wheel nodes connected by a N2 (C2 H4 )3 (DABCO) ligand with accessible nitrogen lone pairs. The coordination is predicted, from first-principles density functional theory, to enable electronic pathways that could facilitate charge carrier mobility. Calculated frontier crystal orbitals indicate extended electronic communication in DMOF-1, but not in MOF-649. This feature is confirmed by band structure calculations and effective masses of the valence band edge. We explain the origin of the frontier orbitals of both MOFs based on the energy and symmetry alignment of the underlying building blocks. The effects of isovalent substitution on the band structure of MOF-649 are considered. Our findings highlight DMOF-1 as a potential semiconductor with enhanced 1D charge carrier mobility along the framework.